EFL STUDENTS’ PERCEPTION REGARDING THE UTILIZATION OF TED (TECHNOLOGY, ENTERTAINMENT, AND DESIGN) TALKS TO ENHANCE THEIR SPEAKING SKILLS - Berliana Sukma Tri Sukarno; Mukhlash Abrar; Saharudin Saharudin; Marzul Hidayat (PROJECT (Professional Journal of English Education), 2024)
This qualitative study investigates the perception of English as a Foreign Language (EFL) students regarding the utility of TED Talks in improving their speaking proficiency. Through interviews and documentation analysis, the study addresses the central query: "How do EFL students perceive the use of TED Talks for enhancing speaking skills?" Findings reveal a positive consensus among participants, indicating that TED Talks serve as a valuable resource for honing speaking abilities. The research highlights that TED Talks stimulate students' enthusiasm for speaking practice, with a preference for engagement during TED Talks sessions over conventional speaking exercises. However, certain challenges such as limited mobile phone access, constrained internet packages, and poor signal conditions hinder optimal utilization of TED Talks. Despite these obstacles, EFL students perceive TED Talks as conducive to speaking skill development, evidenced by observed enhancements in their speaking proficiency. This study underscores the potential of TED Talks as an effective tool for fostering English speaking skills among EFL learners.